Original article Correlation between treatment plan parameters and particular prognostic factors in prostate cancer treated with high-dose-rate brachytherapy (HDR-BT) as a boost - Chicheł, Adam; Kanikowski, Marek; Skowronek, Janusz; Dymnicka, Magdalena; Piotrowski, Tomasz (Journal of Contemporary Brachytherapy, 2009)
Purpose: Certain constraints for target coverage and dose limits in Organs at Risk (OARs) shows some evidence that doses values and homogeneity index in treated volume depends on prognostic factors such as prostate volume, location of urethra and the number of inserted applicators. Our study is to determine the relation between values of the doses in prostate, OARs and particular prognostic factors related to HDR-BT of prostate cancer. Material and methods: The amount of 190 patients with localized prostate cancer were treated with interstitial HDR-BT between July 2006 and July 2007. The HDR-BT was administered as a boost for previously delivered 50 Gy dose from external beam radiotherapy. Dose volume parameters were determined such as: Dmin, Dmax, Dmean, D90, V100, V150 and V200 for prostate and Dmin, Dmax, Dmean, D10 and V100 for urethra and rectum (OARs), respectively. These parameters were correlated with prognostic factors such as: age, staging (TNM), Gleason score, initial PSA level (i-PSA), number of needles and volume of the prostate. Results: The mean value of D90 was 91.3%, range 65.9-102.8%. Mean urethral D10 was 121, 8%, range 78.8-152.9%. Mean rectal D10 was 81.3%, range 37.4-101.0%. Statistically significant relationship was found between staging (TNM), prostate volume, and the number of needles used for implant and increased prostate D90 and decreased V200. The prognostic factor was only the age which was related to increased urethral D10 and Dmax. No correlation was found between any prognostic factor and rectal wall DVH parameters. Conclusions: Increased prostate volume with improved D90 and greater number of implanted needles results in better target coverage (higher V100), better dose distribution (lower V200) and decreased dose delivered to the urethra (lower urethral D10, Dmax), with no evident influence on rectal wall. Further investigation with closed follow-up should give an answer whether the above corresponds with morbidity and outcome.